2014
DOI: 10.22373/lj.v2i1.668
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Pembelajaran Berbasis Masalah pada Materi Titrasi Asam Basa untuk Meningkatkan Keterampilan Generik Sains Mahasiswa Program Studi Pendidikan Kimia

Abstract: This study was a pre-experimental study through one group pretest-posttest design. The objective of the study was to see whether there was an increase in generic science skills of students with problem-based learning model in the group activities. The subjects were the chemistry students of 2nd semester in Teacher Training and Education Faculty of Unsyiah. The data collection was conducted by using the instruments such as group activity and multiple choice of generic science skill. The data of group activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…(Abubakar & Arshad, 2015) their research found that problem-based learning has improved students' problem-solving skills and high order thinking skills. It is also in line with what has been found by (Zakiyah, 2014) that the application of PBL model can improve students' generic science skills by using some indicators, such as direct observation, indirect observation, the law of cause and effect, logical inference and logical framework.…”
Section: Conclusion and Suggestionssupporting
confidence: 90%
See 1 more Smart Citation
“…(Abubakar & Arshad, 2015) their research found that problem-based learning has improved students' problem-solving skills and high order thinking skills. It is also in line with what has been found by (Zakiyah, 2014) that the application of PBL model can improve students' generic science skills by using some indicators, such as direct observation, indirect observation, the law of cause and effect, logical inference and logical framework.…”
Section: Conclusion and Suggestionssupporting
confidence: 90%
“…N-gain achieved in this study includes a high level of achievement (Meltzer, 2002). This shows that problem-based learning can increase positive skills and confidence in problem-solving so as to increase the ability to think creatively, self-learning skills, and self-evaluation (Yoon, 2012) and (Zakiyah, 2014) also stated that the generic ability of science can be improved by problem-based learning models. From the table above it can be seen that the N-gain in addition, additions is higher than the substitution and elimination practices.…”
Section: Generic Science Skills On Organic Chemistry Reaction Practicumsupporting
confidence: 54%
“…It is in line with the study conducted by [16] who stated that learning model affects the improvement of generic science skills. [15] also stated that generic science skills can be improved by using PBL. The indicator of generic science skill of experimental and control group are shown in the following figure: Based on the problem of the study, result and discussion as it is stated above, it can be concluded that the implementation of Problem Based Learning model can improve generic science skills of chemistry teacher candidate students with indicator: logical consistency, abstraction, symbol language, modeling, logical inference, cause and effect as well as scale understanding.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Thus, university is asked to provide students with generic science skills [14]. According to Khamsah in [15] generic science skills can be categorized into 9 indicators, they are: 1 This study is aimed at investigating the improvement of teacher candidate students' generic science skills through the use of problem based learning medel in organic chemistry reactions subject.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil penelitiannya tersebut keterampilan generik pengamatan langsung memperoleh nilai paling tinggi dari indikator yang lain yaitu sebesar 78%. Menurut Brotosiswoyo keterampilan generik pengamatan langsung dan tak langsung termasuk kategori mudah dikuasai (Zakiyah, 2013). Sedangkan keterampilan generik inferensi logika diperoleh 55 %.…”
Section: Pendahuluanunclassified